Enhancement of the Silicon Nanocrystals’ Electronic Structure within a Silicon Carbide Matrix - Soni Prayogi (Universitas Gadjah Mada, 2024)
Using plasma-enhanced chemical vapor deposition (PECVD), a mixed gas of silane (SiH4) and methane (CH4) was diluted with hydrogen (H2) to produce thin films of silicon nanocrystals embedded in a silicon carbide (SiC) matrix. This method prevents the co-deposition of SiH and SiC from high-temperature annealing procedures. This study experimentally explores the improvement of the electronic structure by adjusting two processing parameters according to classical nucleation theory (ratio of SiH4 to CH4 and working gas pressure). The deposited films were examined using ellipsometry spectroscopy, X-ray diffraction, scanning electron microscopy, atomic force microscopy, and photoluminescence to determine grain size, crystal volume fraction, topography, and bond configurations. The results show that increasing the working gas pressure can increase the density of SiC, while increasing the ratio of SiH4 to CH4 can only produce larger grain sizes. This is consistent with how SiC works and grows. Without using a high-temperature annealing procedure, this technique can improve the electrical structure of SiC contained in the SiC matrix formed by PECVD.